2018
DOI: 10.1158/1078-0432.ccr-18-0554
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in Ovarian Cancer Are Characterized by a Highly Activated Phenotype Distinct from that in Melanoma

Abstract: Regulatory T (Treg) cells expressing the transcription factor FOXP3 are essential for the maintenance of immunologic self-tolerance but play a detrimental role in most cancers due to their ability to suppress antitumor immunity. The phenotype of human circulating Treg cells has been extensively studied, but less is known about tumor-infiltrating Treg cells. We studied the phenotype and function of tumor-infiltrating Treg cells in ovarian cancer and melanoma to identify potential Treg cell-associated molecules … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 50 publications
(65 reference statements)
3
85
0
Order By: Relevance
“…Furthermore, Toker et al demonstrated that the Treg cells that infiltrate the ovarian cancer nest are typified by a distinct surface phenotype that differs from the ones found in other types of cancer nests. These cells are characterized by an increased expression of PD-1 and 4-1BB, both of which are associated with an increased suppressive capacity [25]. Additionally, Curiel et al reported that, in the later stages of cancer, Treg cells seem to have a preference towards tumors and ascites and will only rarely accumulate in the draining lymph nodes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Toker et al demonstrated that the Treg cells that infiltrate the ovarian cancer nest are typified by a distinct surface phenotype that differs from the ones found in other types of cancer nests. These cells are characterized by an increased expression of PD-1 and 4-1BB, both of which are associated with an increased suppressive capacity [25]. Additionally, Curiel et al reported that, in the later stages of cancer, Treg cells seem to have a preference towards tumors and ascites and will only rarely accumulate in the draining lymph nodes [11].…”
Section: Discussionmentioning
confidence: 99%
“…TCR inhibition could cause a decrease in the rate of proliferation and impaired functioning in the cells (Y. . (Toker et al, 2018). This reprogramming is applicable through suppressing receptor/ligand interactions for CD25, neuropilin-1 (Nrp-1), and FOXP3 expressed on Tregs.…”
Section: Preferential Ablation Of Intratumoral Tregsmentioning
confidence: 99%
“…2 Treg cells are characterized by the expression of the key transcription factor forkhead box protein 3 (Foxp3), 4 which is essential for maintaining self-tolerance and immune homeostasis. [4][5][6] Treg cells have also been reported in cervical cancer, particularly CSCC; these studies have mostly dealt with Tregs as a whole population and the associated clinical consequences. [4][5][6] Treg cells have also been reported in cervical cancer, particularly CSCC; these studies have mostly dealt with Tregs as a whole population and the associated clinical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Accumulating data have suggested that the progression from HPV infection to (pre)neoplastic lesions is associated with altered local immune responses, which makes cervical cancer an important immunogenic cancer. 2 Treg cells are characterized by the expression of the key transcription factor forkhead box protein 3 (Foxp3), 4 which is essential for maintaining self-tolerance and immune homeostasis. 3 In addition, an increased prevalence of Treg cells in both peripheral blood and tumor tissues has been observed in patients with various cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation